Average Error: 14.1 → 14.1
Time: 18.4s
Precision: 64
$\frac{\left(1 - t\right) \cdot \frac{\sin \left(\left(1 - t\right) \cdot y\right)}{\left(1 - t\right) \cdot y}}{\frac{\sin y}{y}}$
$\frac{\left(1 - t\right) \cdot \frac{\sin \left(\left(1 - t\right) \cdot y\right)}{\left(1 - t\right) \cdot y}}{\frac{\sin y}{y}}$
\frac{\left(1 - t\right) \cdot \frac{\sin \left(\left(1 - t\right) \cdot y\right)}{\left(1 - t\right) \cdot y}}{\frac{\sin y}{y}}
\frac{\left(1 - t\right) \cdot \frac{\sin \left(\left(1 - t\right) \cdot y\right)}{\left(1 - t\right) \cdot y}}{\frac{\sin y}{y}}
double f(double t, double y) {
double r31636 = 1.0;
double r31637 = t;
double r31638 = r31636 - r31637;
double r31639 = y;
double r31640 = r31638 * r31639;
double r31641 = sin(r31640);
double r31642 = r31641 / r31640;
double r31643 = r31638 * r31642;
double r31644 = sin(r31639);
double r31645 = r31644 / r31639;
double r31646 = r31643 / r31645;
return r31646;
}


double f(double t, double y) {
double r31647 = 1.0;
double r31648 = t;
double r31649 = r31647 - r31648;
double r31650 = y;
double r31651 = r31649 * r31650;
double r31652 = sin(r31651);
double r31653 = r31652 / r31651;
double r31654 = r31649 * r31653;
double r31655 = sin(r31650);
double r31656 = r31655 / r31650;
double r31657 = r31654 / r31656;
return r31657;
}



# Try it out

Results

 In Out
Enter valid numbers for all inputs

# Derivation

1. Initial program 14.1

$\frac{\left(1 - t\right) \cdot \frac{\sin \left(\left(1 - t\right) \cdot y\right)}{\left(1 - t\right) \cdot y}}{\frac{\sin y}{y}}$
2. Final simplification14.1

$\leadsto \frac{\left(1 - t\right) \cdot \frac{\sin \left(\left(1 - t\right) \cdot y\right)}{\left(1 - t\right) \cdot y}}{\frac{\sin y}{y}}$

# Reproduce

herbie shell --seed 1
(FPCore (t y)
:name "(1-t) * (sin((1-t) * y) / ((1-t) * y)) / (sin(y) / y)"
:precision binary32
(/ (* (- 1 t) (/ (sin (* (- 1 t) y)) (* (- 1 t) y))) (/ (sin y) y)))